Identification of a Hematopoietic Cell Population Emerging From Mouse Bone Marrow With Proliferative Potential In Vitro and Immunomodulatory Capacity - Marinescu, Catalina-Iolanda; Preda, Mihai Bogdan; Neculachi, Carmen Alexandra; Rusu, Evelyn Gabriela; Popescu, Sinziana; Burlacu, Alexandrina (Frontiers in Immunology, 2021)
There is continuing interest in therapeutic applications of bone marrow-derived mesenchymal stromal cells (MSC). Unlike human counterparts, mouse MSC are difficult to propagate in vitro due to their contamination with adherent hematopoietic cells that overgrow the cultures. Here we investigated the properties of these contaminating cells, referred to as bone marrow-derived proliferating hematopoietic cells (BM-PHC). The results showed that both BM-PHC and MSC had strong immunomodulatory properties on T cells in vitro, with PGE2 and NO involved in this mechanism. However, BM-PHC were stronger immunomodulators than MSC, with CCL-6 identified as putative molecule responsible for superior effects. In vivo studies showed that, in contrast to BM-PHC, MSC endorsed a more rapid xenograft tumor rejection, thus indicating a particular context in which only MSC therapy would produce positive outcomes. In conclusion, bone marrow contains two cell populations with immunomodulatory properties, which are valuable sources for therapeutic studies in specific disease-relevant contexts.